Successive melting of a phase change material bounded in a finned trapezoidal domain - Ahmad, Farooq (2022)
The storage of thermal energy in a trapezoidal aluminum enclosure via melting of PCM phase change material is studied. Experimental observations and numerical simulation are made to examine the process for the phase change of paraffin wax. The development of LHTES: latent heat thermal energy storage system is a promising alternate option to manage the growing imbalance of energy consumption and supply. Successive melting of paraffin Rubitherm-RT35 is designed when it is heated from one side of the frame and the remaining sides are insulated. Two configurations are examined for the heat storage material: (a) paraffin wax only via experimental set up; (b) PCM melting in a fin extended aluminum structure via simulation. From the lab set up, melt fronts of melting PCM for various time lengths are photographed. In second procedure, improvement in thermal conductivity is desired through fin extension by utilizing software Multi-physics Comsol version 5.4. Transient heat conduction and enthalpy function built in the fluid-solid module are hired. Simulation procedure is carried out with fin augmentation. The melting time is notably reduced with enhancing technique of thermal conductivity via fins.